Penerapan Model Pembelajaran Cooperative Integrated Reading And Composition (CIRC) Untuk Meningkatkan Meningkatkan Minat Baca dan Keterampilan Menulis Siswa - Setiawati, Astria; Muammar; Sani, Muhammad Anwar (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The purpose of this study was to improve and enhance reading interest and writing skills of fourth grade students by using the cooperative integrated reading and composition (CIRC) learning model at SDN Inpres Tambe in Indonesian language content. The problems in this study were that the students' desire to read was lacking, the facilities and infrastructure in the form of reading books in schools were lacking, and the use of punctuation marks and spelling was not correct in writing. The type of research used was classroom action research (PTK) which takes place in two cycles. Each cycle is carried out according to the learning implementation plan (RPP) that has been made and is divided into four stages, namely the planning, implementation, observation, and reflection stages. The research subjects were grade IV students, totaling 28 students. The instruments used in this study were observation sheets and questionnaires. The results showed that there was an increase in reading interest and writing skills by applying the CIRC learning model based on the results of the fourth grade students' reading interest questionnaire included in the very strong criteria. This condition is because students like to read, are aware of the benefits of reading and the quantity of reading is also high. Whereas in writing skills the score in cycle I was 74.8 with 67% classical completeness and writing skills were still below standard, judging from the results of classical completeness it had to reach 85%. In cycle II there was an increase in students' writing skills using the CIRC model in that the Indonesian language lesson content was said to be complete, this can be seen from the average grade IV students of 84.8 and their classical completeness of 89%